1999
DOI: 10.1046/j.1365-2125.1999.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone N‐demethylation in human liver microsomes: lack of stereoselectivity and involvement of CYP3A4

Abstract: Aims To investigate the kinetics of CYP-mediated N-demethylation of methadone in human liver microsomes, and examine the role of stereoselectivity and CYP isoforms involved. Methods The kinetics of 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) formation via N-demethylation of rac-, (R)-and (S)-methadone in human liver microsomes prepared from six liver samples were determined by h.p.l.c., and inhibition of metabolic function was studied using isoform-specific chemical inhibitors and monoclonal antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
150
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(159 citation statements)
references
References 34 publications
7
150
1
1
Order By: Relevance
“…CYP3A appears not to mediate ritonavirlopinavir effects on methadone disposition, and, more generally, these results do not support a predominant role for CYP3A in clinical N-demethylation and clearance of single-dose methadone. The preponderance of other clinical evidence also vitiates the longheld notions that CYP3A4 activity determines clinical methadone N-metabolism and clearance, CYP3A4 interindividual variability is a major factor in variable methadone bioavailability, and CYP3A4 mediates methadone interactions with antiretrovirals and other drugs (Ferrari et al, 2004;McCance-Katz et al, 2010), which were extrapolated from in vitro methadone N-demethylation by CYP3A4 (Iribarne et al, 1996;Foster et al, 1999;Gerber et al, 2004;Chang et al, 2011). Strong hepatic and first-pass CYP3A inhibition by troleandomycin, and by ritonavir-indinavir, had no significant effects on methadone plasma concentrations, systemic or apparent oral clearance, hepatic clearance, or bioavailability (Kharasch et al, 2004a(Kharasch et al, , 2009a.…”
Section: Controlmentioning
confidence: 99%
“…CYP3A appears not to mediate ritonavirlopinavir effects on methadone disposition, and, more generally, these results do not support a predominant role for CYP3A in clinical N-demethylation and clearance of single-dose methadone. The preponderance of other clinical evidence also vitiates the longheld notions that CYP3A4 activity determines clinical methadone N-metabolism and clearance, CYP3A4 interindividual variability is a major factor in variable methadone bioavailability, and CYP3A4 mediates methadone interactions with antiretrovirals and other drugs (Ferrari et al, 2004;McCance-Katz et al, 2010), which were extrapolated from in vitro methadone N-demethylation by CYP3A4 (Iribarne et al, 1996;Foster et al, 1999;Gerber et al, 2004;Chang et al, 2011). Strong hepatic and first-pass CYP3A inhibition by troleandomycin, and by ritonavir-indinavir, had no significant effects on methadone plasma concentrations, systemic or apparent oral clearance, hepatic clearance, or bioavailability (Kharasch et al, 2004a(Kharasch et al, , 2009a.…”
Section: Controlmentioning
confidence: 99%
“…Methadone is primarily metabolized by the cytochrome P450 enzyme system, specifically CYP3A4, to 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) [25][26][27]. Although not a substrate for glucuronidation itself, methadone inhibits the glucuronidation of 3 ′ -azido-3 ′ -deoxythmidine (AZT) in vitro [28].…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, it was also observed that methadone-maintained subjects had higher plasma morphine concentrations than non-opioid-dependent controls when given the same i.v. dose, suggesting decreased morphine clearance in this population.Methadone is primarily metabolized by the cytochrome P450 enzyme system, specifically CYP3A4, to 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) [25][26][27]. Although not a substrate for glucuronidation itself, methadone inhibits the glucuronidation of 3 ′ -azido-3 ′ -deoxythmidine (AZT) in vitro [28].…”
mentioning
confidence: 99%
“…The main enzyme responsible for N-demethylation of methadone is CYP3A4, with lesser involvement from CYP1A2 and CYP2D6. 2,18 Current evidence suggests that CYP2B6 may play a very significant role in metabolism as well.…”
Section: Pharmacokineticsmentioning
confidence: 99%